Mastering Church Management - Cousins, Don; Don Cousins; Arthur DeKruyter (Portland Multinomah Press, 1990)
"The mastering ministry series brings together some of the best minds on specific areas of pastoral ministry and presents their insights in a readable, personal way. Each book is co-authored by three church leaders recognized for their experience and expt
Keywords: Church Management